Sustainable Performance and ESG Attractiveness In Increased Value of Banking Companies - Purnamawati, I Gusti Ayu; Jean Marc Dautrey (AKRUAL: JURNAL AKUNTANSI, 2025)
Abstract Increasing company value should be in line with ESG investment, but its implementation is still minimal. The aim of this research by look at other dimensions such as profitability, liquidity, and ESG in banking companies. The research uses secondary data obtained based on annual and financial reports as well as company value in banking companies listed on the Indonesia Stock Exchange in 2020- 2022. The method used in collecting samples in this research is purposive, so the sample is ten banking companies in Indonesia. Multiple linear regression analysis test with Gretl software. The results show that the profitability variable has a positive and significant effect on firm value, but the liquidity variable and ESG variables do not have a significant impact on firm value. By informing sustainability reports containing financial and non-financial information, information regarding company performance can be provided and accounted for to shareholders to satisfy shareholder demands